Phosphate solubilization by endophytic bacteria isolated from banana trees - AMANDA D.M. MATOS (Anais da Academia Brasileira de Ciências, 2017)
Forty isolates of endophytic bacteria isolated from banana tree roots were assessed as to their capacity to solubilize phosphate in a solid culture medium supplemented with different inorganic and one organic source of phosphorus. The amount of phosphorus (P) in each liquid medium was quantified, and an indirect assessment of acid phosphatase activity was performed. All assays had a fully randomized design, with three repetitions. Approximately 67.5% of the 40 isolates assessed in solid medium solubilized phosphorus from tricalcium phosphate and 7.5% of the isolates solubilized phosphorus from soy lecithin; no isolates exhibited P solubilization capacity in medium supplemented with iron phosphate . Acid phosphatase activity was detected in 65% of the isolates; Aneurinibacillus sp . and Lysinibacillus sp. isolates presented with the best solubilization indexes. All of the assessed isolates exhibited a capacity to reduce the potential of hydrogen in liquid medium supplemented with tricalcium phosphate. Isolate EB. 78 ( Bacillus sp.) exhibited P solubilization capacity in solid media when Ca 3 (PO 4 ) 2 and soy lecithin were used as P sources; this isolate significantly reduced the pH of the liquid medium and exhibited acid phosphatase activity. The results of the present study highlight isolates that exhibit variations in their capacity to solubilize P. These isolates should be used in future tests to assess their field performance.